Road Map for Farm Mechanization in Assam State - MANDAL, S.; KUMAR, A.; SINGH, R.K.; NGACHAN, S.V. (Indian Journal of Hill Farming, 2015)
Assam has the largest cultivable plain land in North-East India but power consumption for mechanization is 0.75 kW/ha which is still below the national average of 1.5 kW/ha. For sustainable food grain production and drudgery reduction, mechanization of agriculture is mandatory to an optimum level. An attempt has been made to find out optimum requirement of farm power and machinery for mechanization of major crops of Assam state. The required number has been decided based on appropriate capacity of each machine and area under a particular crop. Results showed that Assam state will require 37,616 numbers of tractors and 43,886 numbers of power tillers which will increase the density of tractor and power tiller up to 13.7 and 16.1 per thousand ha, respectively. Estimated requirement also includes 29,257 units of mould board plough, 42,839 units of cultivators, 52,245 units of paddy transplanter, 4,180 units of combine harvester and some other specific implements and machinery.